Activity patterns of the Brown Vine snake Oxybelis aeneus (Wagler, 1824) (Serpentes, Colubridae) in the Brazilian semiarid - Mesquita, Paulo C. M. D. (2022)
The Brown Vine snake, Oxybelis aeneus (Wagler, 1824), is widely distributed from the United States to Argentina. 113 specimens encountered in the field and 39 individuals from scientific collections were analyzed and we determined patterns of diet, habitat use, and daily and seasonal activity. Oxybelis aeneus can be found to be active year round, especially during the dry and warmer months. Daily temperature poorly describes its activity as it seems to be more active around 31 to 35°C. During the hours of inactivity the species tends to chose higher branches than when active. The snakes choose spiny trees as retreat sites and spineless trees as foraging sites. We suggest that the high abundance of O. aeneus makes it an appropriate model organism for studies on activity patterns of snakes in semi-arid environments. © Koninklijke Brill NV, Leiden, 2012.